Challenges Faced by Healthcare Professionals in Delivering Emergency, Medical, and Gynaecology Services at Rajshahi Medical College Hospital (Journal of Bio-Science, 2026)
Healthcare services play a crucial role in maintaining population health by providing timely medical care and disease management. However, healthcare professionals often encounter various challenges that may affect the quality and efficiency of service delivery. This study aimed to explore the challenges faced by healthcare professionals in enhancing healthcare services in the Emergency, Medicine, and Gynaecology departments of Rajshahi Medical College Hospital (RMCH), Bangladesh. A descriptive cross-sectional study was conducted from August 2023 to March 2024 among 238 healthcare professionals, including doctors, nurses, and technicians. Data were collected using a structured dichotomous questionnaire and analyzed using SPSS version 22.0 with descriptive statistics. The findings revealed that 61.76% of respondents reported satisfaction with the existing infrastructure, while 82.35% confirmed the availability of essential drugs and medical equipment. Additionally, 75.63% indicated that government funding was adequate, and 79% believed that current healthcare policies and regulations were effective. Despite these positive perceptions, several challenges were reported, including shortages of healthcare personnel (41.17%), limited technological resources (40.34%), inappropriate population-to-bed ratios (55.04%), and difficulties in managing emerging and re-emerging diseases (87.81%). The study concludes that although key healthcare resources such as drugs, equipment, and policy support are generally adequate, significant operational challenges remain. Addressing workforce shortages, improving technological capacity, and optimizing hospital resource allocation are essential to further strengthen healthcare service delivery in tertiary-level hospitals in Bangladesh.J. Bio-Sci. 34(1): 12-21, 2026